Axon pathology in mouse models of Huntington's disease - Marangoni, Martina (2014)
Axon or synapse dysfunction parallels or precedes symptom onset in many neurodegenerative disorders. In some of these conditions, not only do axon and synapse loss determine the course of pathology, but protection of those neuronal compartments is mandatory to alleviate the disease. Whether this is also the case in Huntington’s disease (HD), a devastating neurodegenerative disorder characterised by progressive deterioration of both physical and mental abilities and inevitable early death, remains unclear. Present therapeutic strategies do not address protection of axons and synapses, which may help explain why there is no effective treatment currently in use. Moreover, an accurate characterisation of the development of axon pathology relative to neuronal loss and to the deposition of mutant-Huntingtin (mHTT) aggregates, neuropathological hallmark of HD, is lacking.